Phenology of Campomanesia adamantium (Cambess.) O. Berg in Brazilian Cerrado - Leão-Araújo,Érica Fernandes (2019)
Abstract Campomanesia adamantium is a fruit tree native to Cerrado and important for human consumption as food, herbal medicine and even in the beverage industry. The aim of this study was to evaluate the vegetative and reproductive phenology of C. adamantium plants in the region of Ipameri-GO, the synchronization of phenophases and the correlation with climatic data. Rainfall, relative humidity, average, maximum and minimum temperature, as well as sprouting, flowering and fruiting data of C. adamantium plants were collected between September and December of 2016 and 2017. Graphs were plotted for climatological data and phenological phases. Phenophase synchrony analysis and correlation of these phases with the climate of the region were performed. Sprouting and flowering began before the first rains of the rainy season and the peak of these phenophases occurred in October. Fruiting began in October and peak was observed in November. Sprouting is highly synchronous from the second ten days of October and flowering reveals high synchronicity between the second half of October and the first half of November. Fruiting is considered highly synchronous from the second half of November. Not all plants reach reproductive stages. Sprouting and fruiting are related to the occurrence of rainfall and increase of air RH. Flowering has no correlation with rainfall, air RH and temperature.